Gaussian Bayesian network comparisons with graph ordering unknown - Zhang, Hongmei; Huang, Xianzheng; Han, Shengtong; Rezwan, Faisal I.; Karmaus, Wilfried; Arshad, Syed Hasan; Holloway, John W. (Elsevier, 2020)
A Bayesian approach is proposed that unifies Gaussian Bayesian network constructions and comparisons between two networks (identical or differential) for data with graph ordering unknown. When sampling graph ordering, to escape from local maximums, an adjusted single queue equi-energy algorithm is applied. The conditional posterior probability mass function for network differentiation is derived and its asymptotic proposition is theoretically assessed. Simulations are used to demonstrate the approach and compare with existing methods. Based on epigenetic data at a set of DNA methylation sites (CpG sites), the proposed approach is further examined on its ability to detect network differentiations. Findings from theoretical assessment, simulations, and real data applications support the efficacy and efficiency of the proposed method for network comparisons.
Keywords: Bayesian methods; DNA methylation; Single Queue Equi-Energy; Differential Gaussian Bayesian network; Variable selections; Ordering